Responsabilidade socioambiental e sustentabilidade no ambiente empresarial: do capital aos trabalhadores de Brumadinho/MG - Oliveira, Ariani Avozani (2020)
The research addresses the socio-environmental responsibility and sustainability policies used by Vale S.A., one of the largest global mining companies, which extracts iron ore at the Córrego do Feijão Mine, in the municipality of Brumadinho/MG, and adopts the Environmental Quality Management model certified by ISO 14001, in order to guarantee their permanence in the international market. An analysis is made regarding the company's environmental management, considered to be effective, at least until January 25, 2019, when the BI dam, located in the mine area, broke. The disaster killed 312 workers, among their own employees and third parties, 248 died. Even after the disruption and due to the social and environmental impacts caused to the local community, the Mine's activities continued in full operation. Annually, the company presents sustainability reports, whose positive character, indicates the interfaces between the implementation and effectiveness of socioenvironmental and sustainable policies, adopted in the work environment. The dam rupture instigated doubts as to the reality of the work environment and the company's pretension to accumulate capital since it did not cease its activities at the Mine, to avoid disaster, even when it observed failures in the rainwater drainage system. The objective is to answer the following question: “starting from the verification of the non-observances regarding the work safety norms and the socioenvironmental and sustainable policies in the business environment and the consequences caused to Vale workers, affected by the accident, it can be said that Was there a distortion of the essential objective of the social and economic dimension of sustainability in favor of the company's capital accumulation? ” The understanding of the context of the disaster is verified by the labor perspective, analyzing the socio-environmental and sustainable policies and the labor safety and health standards disrespected by Vale S.A. and the consequences caused to the workers victimized. The method employed is the hypothetical-deductive and, of a descriptive nature, seeks to establish a relationship between the variables identified and analyzed in the investigated phenomenon. As for the concern with the rules of work safety, health and well-being of workers, as opposed to the accumulation of capital, the monographic procedure, and specific case study is used as a technique, through the application of field research. Thus, a structured interview is held with victims and authorities involved in the tragedy, such as the Labor Prosecutor and the Labor Auditor and the Trade Union Representative of the Category of Employees of the region, aiming at the detailing of the environment and working conditions in Mina. The results lead to the confirmation of the accused hypotheses regarding the non-compliance with the norms of the Risk Management Program, required by NR-22, in addition to the non-compliance with the legislation related to the prevention of workers' health and safety. It is concluded that: the consequences of the disaster confront social rights, constitutional guarantees and the labor environment, related to socio-environmental and sustainable policies, to the benefit of the accumulation of capital. This occurs in the face of the current dominant economic, social and legal policy in Brazil and the world, employed to the detriment of the working class.